2012
DOI: 10.1111/j.1442-1984.2011.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination of Pilosocereus arrabidae (Cactaceae) from a semiarid region of south‐east Brazil

Abstract: We evaluated the effect of temperature regimes (six constant and four alternating temperatures), light qualities (five red : far red ratios) and water potentials (YW; seven NaCl and polyethylene glycol 6000 [PEG] solutions) on the percentage and germination rate, as well as the post-seminal development morphology, that allow Pilosocereus arrabidae seeds to germinate in a hot semiarid climate on the south-eastern Brazilian coast. The results showed that seeds germinated similarly between constant and alternatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(70 reference statements)
1
11
0
1
Order By: Relevance
“…Although some studies have demonstrated that the requirement of alternating temperatures is common among species in arid and semiarid ecosystems (Meiado et al, 2012b), Martins et al (2012) found that a constant temperature was more favorable to the germination of seeds from Pilosocereus arrabidae (Lem.) Byles and Rowley.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have demonstrated that the requirement of alternating temperatures is common among species in arid and semiarid ecosystems (Meiado et al, 2012b), Martins et al (2012) found that a constant temperature was more favorable to the germination of seeds from Pilosocereus arrabidae (Lem.) Byles and Rowley.…”
Section: Resultsmentioning
confidence: 99%
“…), Pilosocereus arrabidae (Martins et al . ), Opuntia tomentosa (Olvera‐Carrillo et al . ), Trichocereus terscheckii (Ortega‐Baes & Rojas‐Aréchiga ) , Echinocactus platyacanthus and Ferocactus flavovirens (Rojas‐Aréchiga et al .…”
Section: Discussionmentioning
confidence: 99%
“…The osmotic potentials used were: 0.0, −0.25, −0.5, −0.75, −1.0, −1.25 and −1.5 MPa. These different potentials were found in the restinga ( Martins et al 2012 ). PEG 8000 and NaCl solutions were prepared according to Villela and Beckert (2001) and Salisbury and Ross (1992) , respectively.…”
Section: Methodsmentioning
confidence: 73%
“…Casuarina equisetifolia seeds had a fast physiological response when in contact with water, and germination started in 3–4 days after water uptake in optimal germination temperatures (30 and 35 °C). For small-seeded species, high germination rate is crucial for the recruitment of new individuals, mainly in environments with water restrictions, as is the case in the restingas ( Martins et al 2012 ). The capacity to germinate under a wide range of temperature conditions, including low (15 °C) and high alternating temperatures (40/20 °C), although with decrease in the germination rate, is also an important factor for a population to become naturalized in the restinga, where the temperatures can range from 21 to 31 °C (mean of 25 °C) inside the patches, and from 19 to 44 °C (mean of 30 °C) in open areas ( Matos 2014 ).…”
Section: Discussionmentioning
confidence: 99%